Facebook Usage In Learning English Writing Skill And In Improving Students’ Motivation - Rahman, Abdur; Anita Aulia, Ersa (Jurnal Ilmiah Mandala Education (JIME), 2024)
One of the applications of information technology used to this research is Facebook. It is very most famous and there are many students use it. Therefore, Facebook is used as a learning media for English writing skill in the schools. Many teachers found that most the students used Facebook in class. They ignore to study and only focus on Facebook. This research is to find the influence of Facebook on learning English and students’ motivation in writing skill. Therefore, using Facebook as a learning tool for students is investigated with the title "Facebook Usage in Learning English Writing Skill and In Improving Students’ Motivation”. This research is to know the frequency of students’ use of Facebook for English writing skill and to know the influence of Facebook usage in English writing skill and in improving students’ motivation. The participant is students of STIPAR Soromandi Bima, and the sample is two classes of second Semester that consist of 53 students. Methodology used is in correlation design by using quantitative method. The data collecting technique is giving the questionnaire. The data analyzing technique uses a hypothesis test by using the correlation of product moment formula to measure the variables. The finding of this research shows that students often use Facebook for English writing skill. It is proven by the average score is 82.79, and 17 students very often, 19 students often, and 17 students a little often use Facebook for writing skill. While the result of statistical analysis it is found that rxy1 is 0.995 with the average score is 79.39 and rxy2 is 0.994 with the average score is 84.53 and r-table is 0.279. Because the rxy value was greater than r-table, it can be concluded that there are a positive influence of Facebook on English writing skill and students’ motivation.